2017
DOI: 10.1038/s41431-017-0007-0
|View full text |Cite
|
Sign up to set email alerts
|

CHARGE syndrome: a recurrent hotspot of mutations in CHD7 IVS25 analyzed by bioinformatic tools and minigene assays

Abstract: CHARGE syndrome is a rare genetic disorder mainly due to de novo and private truncating mutations of CHD7 gene. Here we report an intriguing hot spot of intronic mutations (c.5405-7G > A, c.5405-13G > A, c.5405-17G > A and c.5405-18C > A) located in CHD7 IVS25. Combining computational in silico analysis, experimental branch-point determination and in vitro minigene assays, our study explains this mutation hot spot by a particular genomic context, including the weakness of the IVS25 natural acceptor-site and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
(1 reference statement)
1
11
0
Order By: Relevance
“…Only one patient had a hot spot of intron variant c.5405 − 7G > A. In our study, it was reported to be pathogenic [ 25 ]; this finding was consistent with the results of two previous studies, which indicated that the CHD7 variant was not the primary cause of KS because only 3–5% of nIHH/KS patients had a CHD7 variant [ 23 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…Only one patient had a hot spot of intron variant c.5405 − 7G > A. In our study, it was reported to be pathogenic [ 25 ]; this finding was consistent with the results of two previous studies, which indicated that the CHD7 variant was not the primary cause of KS because only 3–5% of nIHH/KS patients had a CHD7 variant [ 23 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, whether the gene expression and chromatin structure are correct may be the pathogenesis of CS caused by the CHD7 mutation. The CHD7 gene may be regulated by epigenetic and signaling pathways that function as chromatin remodeling factors and may directly or indirectly affect ectodermal lineage genes (Platt et al, 2017;Legendre et al, 2018;Goodman and Bonni, 2019). Abnormal antenatal examinations were present in ten of the 12 patients.…”
Section: Used the Acronym "Charge" (Ocular Coloboma [C] Heart Malform...mentioning
confidence: 99%
“…Depending on the objectives of the study, different experimental settings and laboratory protocols can be used. To give an overview of the potential applications of the pDESTsplice and pSpliceExpress vectors, we have compiled 25 published studies [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ], in which these minigene systems were used ( Table 1 and Table 2 ). In most of the works, the usage of pSpliceExpress has been described ( n = 18).…”
Section: Studies Using the Pdestsplice And Pspliceexpress Vectorsmentioning
confidence: 99%
“…However, other procedures were also applied. Legendre et al performed a nested RT-PCR within the region of the lariat structure to determine the branch point [ 51 ]. After PCR, the amplicons were differentiated in size by fluorescent capillary electrophoresis instead of a gel electrophoresis [ 51 ].…”
Section: Studies Using the Pdestsplice And Pspliceexpress Vectorsmentioning
confidence: 99%
See 1 more Smart Citation